PENGEMBANGAN RANCANGAN STANDAR PROSEDUR OPERASIONAL (SPO) GEMPA BUMI DI RUMAHSAKIT TINGKAT II ISKANDAR MUDA BANDA ACEHPENGEMBANGAN RANCANGAN STANDAR PROSEDUR OPERASIONAL (SPO) GEMPA BUMI DI RUMAHSAKIT TINGKAT II ISKANDAR MUDA BANDA ACEH - Rasbainy Hasibuan; Mudatsir .; Didik . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Hospitals are health care institutions that provide full-scale personal health services that provide inpatient, outpatient, and emergency care services. Army Hospital in addition to carrying out its main duty to provide health services also play an active role in providing assistance to victims of disasters. The purpose of this study is to find out how the development of the Standard Operational Procedure (SPO) design of an earthquake in the Iskandar Muda Banda Aceh Level II hospital. The research design used qualitative approach with development researchmethod and field observation result. The respondent in this research is nursing staff and safety facility management (MFK) officer of Level II Hospital of Iskandar Muda Banda Aceh for 8 people, consisting of officer Management of 2 persons and paramedic 6 people, the research was conducted in Bandaran Aceh Iskandar Muda II Hospital on 18 May to 05 June 2017. The results showed that this research has resulted in an operational standard based on disaster management of Tk II Iskandar. Produce a SPO system that is in line with the hospital planning used to evaluate the previous SPO. Expected to provide input on the policy and SPO applied in the framework of disaster management in hospital, therefore SPO needs to be tested and socialization for disaster preparedness preparedness in hospital. The result of SPO development used in Iskandar Muda Banda Aceh kindergarten II hospital can be run properly